2019
DOI: 10.1111/1440-1630.12606
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of service dogs on participation in daily occupations by veterans with PTSD: A pilot study

Abstract: Introduction Post traumatic stress disorder (PTSD) resulting from military service can seriously impact quality of life. There is support for the use of service dogs amongst people with PTSD in managing symptoms by reducing anxiety and depression. To date, few studies have investigated this phenomenon comprehensively, particularly in relation to enhancing participation in daily occupations. Methods We explored the experience of a group of ex‐serving members of the Australian military with PTSD, who had partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Eight research papers detail the efficacy of interventions (Bracciano et al., 2012; Classen, Cormack, et al, 2014; Classen, Monahan, Canonizado, & Winter, 2014; Krpalek, Achondo, Daher, & Javaherian, 2020; McLaughlin & Hamilton, 2019; Rogers, Mallinson, & Peppers, 2014; Speicher, Walter, & Chard, 2014; Wortman et al., 2018) and two report on occupational performance issues related to military veterans (Dutra, Eakman, & Schelly, 2016; Gregg, Kitzman, & Shordike, 2016). One research paper reported intervention efficacy for military personnel (Beck et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight research papers detail the efficacy of interventions (Bracciano et al., 2012; Classen, Cormack, et al, 2014; Classen, Monahan, Canonizado, & Winter, 2014; Krpalek, Achondo, Daher, & Javaherian, 2020; McLaughlin & Hamilton, 2019; Rogers, Mallinson, & Peppers, 2014; Speicher, Walter, & Chard, 2014; Wortman et al., 2018) and two report on occupational performance issues related to military veterans (Dutra, Eakman, & Schelly, 2016; Gregg, Kitzman, & Shordike, 2016). One research paper reported intervention efficacy for military personnel (Beck et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In two animal‐assisted therapy (AAT) studies, investigators reported improvements in human physical, social, emotional, and cognitive functioning for military veterans (McLaughlin & Hamilton, 2019; Wortman et al., 2018). Wortman et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations